Development Aid and Economic Growth : A Positive Long-Run Relation - Reddy, Sanjay (IMF Working Papers; Working Paper ;, 2009)
We analyze the growth impact of official development assistance to developing countries. Our approach is different from that of previous studies in two major ways. First, we disentangle the effects of two kinds of aid: developmental and non-developmental. Second, our specifications allow for the effect of aid on economic growth to occur over long periods. Our results indicate that developmental aid promotes long-run growth. The effect is significant, large and robust to different specifications and estimation techniques.